Comment on Kalra S, Arora S, Kapoor N. (J Pak Med Assoc. 2023;73:1544-5) Use of Dairy Products in People Living with Diabetes - Prabhakar Pranav Kumar (Journal of the Pakistan Medical Association, 2023)
Dear Editor, I am writing to express my thoughts on the recent paper titled "Use of Dairy Products in People Living with Diabetes." As someone who is deeply concerned about the well-being of individuals with diabetes and the evolving landscape of dietary recommendations for managing this condition, I found this research to be both informative and timely.1 Dairy product consumption could impact the susceptibility to type 2 diabetes mellitus (T2DM), but the results from different studies have been contradictory. Additionally, there has been limited exploration of the wide range of dairy product types. A slight elevation in daily consumption of dairy items like low-fat dairy, cheese, and yogurt might play a role in T2DM prevention. However, this hypothesis requires validation through randomized controlled trials.2 The paper provides a comprehensive overview of the role of dairy products in the diets of people living with diabetes. It is clear that dietary choices play a crucial role in managing blood glucose levels and overall health for those with diabetes. While the authors acknowledge the potential benefits of dairy consumption, such as the rich source of essential nutrients like calcium and vitamin D, they also highlight some of the challenges and concerns related to dairy consumption among this population. Continues...